Pengaruh Daya Tarik Wisata dan Promosi Media Sosial Terhadap Minat Berkunjung Kembali Wisatawan di Flora Wisata Santerra de Laponte Pujon - Kusmawati, Fika Indah; Permatasari, Ita Rifiani (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study aims to determine the extent to which tourist attraction and social media promotion affect tourists' revisit interest in Flora Wisata Santerra de Laponte Pujon. This research is quantitative research. Data was obtained through observation, documentation and questionnaires. Sampling using non probability sampling with purposive sampling technique with a sample size of 100 respondents. Data analysis using multiple linear regression analysis and hypothesis testing. Based on the results of the analysis, it was found that partially the tourist attraction variable (X1) and the social media promotion variable (X2) both variables had a positive and significant effect partially on the variable interest in visiting tourists again. Based on the results of the analysis simultaneously also showed Ho was rejected and Ha was accepted. This means that the tourist attraction variable (X1) and social media promotion (X2) partially or simultaneously had a positive and significant effect on the variable of interest in visiting tourists again. From the results of this study, it is hoped that the management of Flora Wisata Santerra de Laponte can improve the quality and innovation in developing tourist attractions and pay attention to social media promotion strategies.